Forensic Examination and Identification of Writing Inks on Documents: Fatima Fatima - Fatima, Fatima Fatima (International Journal for Electronic Crime Investigation, 2020)
Ink analysis plays a significant role in questioned document examination, a discipline of forensicscience. Writing inks based on their chemical substances such as solvents, resins, colorants as dyesor pigments, may be distinguished by applying two step methodology including non-destructive orvisual examination and destructive or chemical analysis. Both approaches involve identification andcomparison techniques by contributing certain advantages to the investigation such as Thin LayerChromatography has been marked for a long time. However, forensic scientists have the availabilityof evolutionary methods that led to the use of less destructive techniques including spectroscopy thatminimizes the scope of previous separation techniques. This review paper delivers an outline oftechniques/methods including spectroscopic and chromatographic development with possibleadvantages or drawbacks. The acquired results should be evaluated accurately by paying moreconsideration as providing reliable findings in the court of law is certainly of central significance.